A rare case of primary cutaneous diffuse large B cell lymphoma, leg type with metastasis - Bose, Agni K.; Khade, Pandharinath K.; Kharkar, Vidya D. (International Journal of Research in Dermatology, 2021)
Primary cutaneous diffuse large B cell lymphoma, leg type (PCDLBCL-LT) is a rare and aggressive type of primary cutaneous B cell lymphoma (PCBCL), which represents 10-20% cases of PCBCL. It has a 40-50% recurrence rate and 5 year survival rate of 50%. Here, we present a case of an 86 year old female who presented to us with complaints of slightly tender annular plaques with an oedematous base present over bilateral lower limbs and pitting oedema. Histopathological examination from the annular lesion showed normal epidermis, grenz zone and a dense lymphoid infiltrate involving almost the entire dermis. Immunohistochemistry confirmed histological findings, atypical cell were positive for CD20 and MUM1 protein with focal expression of BCL 6 which is rare. Based on the above findings, we made a diagnosis of diffuse large B cell lymphoma-leg type and started her on palliative radiotherapy. As PCBCL-LT is rare and aggressive lymphoma, we present this case to review literature and summarise its clinical features.